A Mentalizing‐Based Approach to Family Mediation: Harnessing Our Fundamental Capacity to Resolve Conflict and Building an Evidence‐Based Practice for the Field*. (January 2015) - Howieson, Jill; Priddis, Lynn
<x xml:space="preserve">Abstract</x> This article presents the results of a research study into mentalizing in family mediation. The study employed a mixed‐method approach, which included quantitative and qualitative empirical analysis of mediation transcripts and postmediation surveys. The research identified that, when the mediators adopted a mentalizing stance to facilitate the parties to engage their mentalizing capacities and, in particular, to mentalize for the child, the mediation process became more constructive and meaningful. The article makes recommendations for incorporating a mentalizing‐based approach into the research and education of mediation and building an evidence‐based practice for the field. Key Points for the Family Court Community Empirical evidence into the interventions used in family mediation Introducing a mentalizing‐based approach to practice Creating an environment for constructive family dispute resolution Methods to keep the best interests of the child in mind in mediation